Cytogenomic characterization of small supernumerary marker chromosomes in patients with pigmentary mosaicism - Navarrete-Meneses, M. P.; Ochoa-Mellado, I.; Gutiérrez-Álvarez, R.; Martínez-Anaya, D.; Juárez-Figueroa, U.; Durán-McKinster, C.; Lieberman-Hernández, E.; Yokoyama-Rebollar, E.; Gómez-Carmona, S.; Del Castillo-Ruiz, V.; Pérez-Vera, P.; Salas-Labadía, C. (Frontiers in Genetics, 2024)
Introduction. The combination of gene content on the marker chromosome, chromosomal origin, level of mosaicism, origin mechanism (chromothripsis), and uniparental disomy can influence the final characterization of sSMCs. Several chromosomal aberrations, including sSMCs, have been observed in 30–60% of patients with pigmentary mosaicism, and in more than 80%, chromosomal abnormalities are present in the mosaic state. In patients with pigmentary mosaicism the most representative chromosomes involved in sSMCs are 3, 5, 6, 9, 10, 13, 15, 18, 20, and X. In this study, we included the complete clinical, cytogenetic, and molecular characterization of seven patients with pigmentary mosaicism associated with the presence of SMCs of different chromosomal origins. Methods. The patients were diagnosed by the Genetics and Dermatology Department of three different hospitals. Cytogenetic and FISH analyses were performed on peripheral blood, light skin, and dark skin. FISH analysis was performed using different probes, depending on the marker chromosome description. Different array analysis was performed. Results To date, of the seven cases studied, the chromosomal origins of six were successfully identified by FISH or array analysis. The chromosomes involved in SMCs were 6, 9, 15, and 18, X. The most frequently found was the centric minute structure. Discussion. To date, this group of 7 patients constitutes the largest clinical and cytogenetically finely described study of cases with pigmentary mosaicism associated with sSMCs. Undoubtedly, analysis of the two skin types is a fundamental part of our study, as numerical differences may occur in the cell lines found in each skin type. The knowledge generated in this study will help delineate a very heterogeneous entity more accurately, and in the future, analyzing more patients with PM will likely establish a more definite association with the presence of this genetic alteration.